Comparison of the Quality of Life in Elderly With Young and Middle Age Chronic Renal Failure Patients - Masomeh Rambod; Foroogh Rafii; Mohammad Khabaz Shirazi; Fariba Ghodsbin; Seyed Taghi Heydari (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The aim of this study was to compare the quality of life in elderly with the young and middle age chronic renal failure Patients. Methods & Materials: This cross-sectional study of 202 chronic renal failure patients included young (age≤40 years), middle age (41-59 years), and elderly (age≥60 years) patients. The subjects were selected by census method. The data were collected using the "Ferrans and Powers quality of life index- dialysis version" and were analyzed using SPSS-14 with one-way ANOVA and Scheffe’s test. Results: In general, 43.6%, 40.1% and 16.3% of the participants were elderly, middle age and young patients respectively. There were no significant differences in overall quality of life between the three groups (F=1.51, P>0.05). Socioeconomic familial subscale of quality of life was not statistically different in the groups (P<0.05). However, psychological/spiritual and health and functioning subscale of quality of life were not different between the groups (P>0.05). Conclusion: This study indicated that socioeconomic familial subscale of quality of life in young patients was lower than elderly and middle age. Therefore, comprehensive insurance and referring to renal and transplant support society for young patients are suggested in order to improve the patients’ quality of life, especially in the socioeconomic domain.